PENGARUH KECERDASAN MORAL DAN KECERDASAN SPIRITUAL TERHADAP KESADARAN SOSIAL DENGAN BUDAYA KAMPUS SEBAGAI VARIABEL MODERASI PADA MAHASISWA TADRIS IPS IAIN PAREPARE - Jumaisa Jumaisa; Fawziah Zahrawati B; Andi Aras (STKIP Singkawang, 2023)
This study aims to analyze the effect of moral intelligence and spiritual intelligence on campus culture as a moderating variable on students’ social awareness. This research is classified as quantitative research. The population in this study were students in the Tadris IPS study program, Faculty of Tarbiyah IAIN Parepare class 2018-2021, totaling 176 students. The sample in this study was 122 students whose determination of the number of samples referred to the Slovin formula. Data collection techniques using questionnaires and documentation. Research hypothesis testing was carried out with the help of SmartPLS software. The findings of this study are: (1) there is a positive and significant effect of moral intelligence on students’ social awareness with P Values of 0.002 < 0.05, (2) there is a positive and significant effect of spiritual intelligence on students’ social awareness with P Values of 0.013 < 0, 05, (3) campus culture cannot moderate the effect of moral intelligence on students’ social awareness with P Values 0.062 > 0.05, and (4) campus culture can moderate the effect of spiritual intelligence on students’ social awareness with P Values 0.005 < 0.05. The effect of moral intelligence and spiritual intelligence with campus culture as a moderating variable on students’ social awareness is 58.8%. From these findings, it can be concluded that it is necessary to pay attention to moral intelligence, spiritual intelligence, and campus culture because they have a positive and significant effect on students’ social awareness.